Description of Learning Achievement of School-Age Children in Tapowolo State School, South Solor Sub-District, East Flores District - Marselus Sapeama Herin; Intje Picauly; Soni Doke (Universitas Nusa Cendana, 2022)
Learning achievement is an investment to improve the quality of human resources. This study described the learning achievement of school-age children according to the variables of parenting nutritional status, parental education level, parental occupation, family income and the number of family members. The type of research was a descriptive study with an observational method. This research was carried out of the Tapowolo State Elementary School, South Solor District, East Flores Regency, in December 2020- January 2021. A sample of 57 students was taken using a total sampling technique. Data was collected using questionnaires and observations. The results showed that most respondents had poor learning achievement with poor parenting, low parental education, low family income, and small family members (70,2%, 82,5%, 87,7%, 89,5%, respectively). However, most respondents had good nutritional status (84,2%). Children's learning achievement can be improved through parents' supportive roles, even though parents are busy at work. Healthy and balanced food intake need to be considered to support growth and development and good learning achievement.